The investigation of ²³⁹⁺²⁴⁰Pu, ⁹⁰Sr and ²³⁷Cs background radiation levels in soil samples in some provinces in the north of Vietnam - Nguyen , Van Khanh; Nguyen Huu Quyet, Huu Quyet; Bui , Dac Dung; Nguyen , Thi Thu Ha; Duong , Duc Thang; Le , Thi Hoa; Nguyen , Huyen Trang; Pham , Tuan Nam; Duong , Van Thang (Nuclear Science and Technology, 2026)
This study was conducted to investigate the background levels of plutonium (239+240Pu), strontium (90Sr), and cesium (137Cs) in the topsoil of some provinces in northern Vietnam. Thirty-one soil samples were collected between October 2020 and January 2022. In the samples, the specific activities of 137Cs were measured directly by gamma spectrometry, while the specific activities of, 239+240Pu, and 90Sr were measured by alpha spectrometry, and beta counting, after the radiochemical separation procedures respectively. The concentrations were observed in the range of (0.768–2.129) Bq/kg dry weight (DW) for 137Cs, (0.018–0.058) Bq/kg DW for 239+240Pu, and (0.022–0.697) Bq/kg DW for 90Sr, with average values are (1.393 ± 0.196) Bq/kg DW, (0.039 ± 0.014) and (0.129 ± 0.011) Bq/kg DW, respectively, which are relatively lower than the reported values in the neighboring country. The average recovery efficiencies for radiochemical separation of 239+240Pu and 90Sr were 63.8% and 52.0%, respectively. The minimum detectable activity (MDA) for 90Sr, 239+240Pu, and 137Cs are 0.012 Bq/Kg DW, 0.004 Bq/Kg DW, and 0.1 Bq/Kg DW, respectively.